Effects of supplementing baker's yeast (Saccharomyces cerevisiae) and yeast glucan on growth performance, nutrient digestibility and meat quality of broiler chicken - Mohamaddin, Nabila (2017)
Increasing concerns regarding overuse of antibiotics in broiler has promoted extensive investigation into alternatives to the use of sub-therapeutic antibiotics such as the used of yeast products. Saccharomyces cerevisiae, which is also known as "Baker Yeast" is rich in crude protein (40-45%) and vitamin B complex. Yeast products have been widely reported as successful growth promoter in poultry industry. There is no relevant information on the meat quality parameter, abdominal fat in broiler fed with yeast, and also blood profile parameter in broiler chicken. Therefore, these parameters need to be investigate for additional information on the effects of yeast products on broilers. The purpose of this study was to compare the levels of baker’s yeast and to study the effects of non-antibiotic feed additives, that is baker’s yeast and yeast glucan on broiler performance. The first experiment involved a total of 200 a day-old broilers (Cobb 500) and were randomly divided into five treatments, four replicates with 10 birds each. The treatments were T1: control; T2: 0.1% baker’s yeast; T3: 0.2% baker’s yeast; T4: 0.4% baker’s yeast; and T5: 0.8% baker’s yeast. For the second experiment, 200 a day-old broilers were randomly divided into four treatments, five replicates with 10 birds each. The treatments were T1: control; T2: probiotic (best level of baker’s yeast from first experiment); T3: prebiotic (MacroGard® yeast glucan); and T4: antibiotic (virginiamycin). The individual body weight and feed intake were recorded weekly, and at day 42, the chickens were slaughtered to determine carcass quality, collection of ileal and ceacal digesta, blood collection, and gut morphology. For the first experiment, data on performances, nutrient digestibility, carcass characteristics, bacteria count, and gut morphology were collected, whereas for the second experiment, data on performances, nutrient digestibility, meat quality, bacteria count, gut morphology, and blood profile were collected. The results of this experiment showed that addition of baker’s yeast (probiotic) and yeast glucan (prebiotic) to broiler’s feed improved body weight compared to control diet. Similar result was also observed in the feed conversion ratio, where both baker’s yeast and yeast glucan showed the lowest FCR followed by control treatment. However, carcass dressing rates were not affected by the non-antibiotic feed additives. The nutrient digestibility by the broiler improved when baker’s yeast and yeast glucan were fed to the birds. Addition of both baker’s yeast and yeast glucan to broiler’s feed had improved the tenderness of the broiler’s meat and gut morphology of the broiler (P<0.05). Other than that, baker’s yeast had improved immunity through WBC reduction. In addition, baker’s yeast and yeast glucan supplementation had reduced the abdominal fat content of the birds. Moreover, the inclusion of baker’s yeast in broiler’s feed has enhanced the population of beneficial bacteria such as Lactobacillus spp. and reduced the colonization of pathogenic bacteria such as E. coli. It has been concluded that baker’s yeast has improved the performance of the broiler chicken. Thus, these can be used as antibiotic alternatives in broilers feed.